(untitled) (The Review of Diabetic Studies, 2024)
Stroke remains a significant public health issue and a leading cause of long-term disability in the United States. This article aims to provide primary care providers with evidence-based guidelines for post-stroke management, emphasizing the needs of the elderly population, particularly those aged 85 and older. The critical window for initiating rehabilitation is highlighted, with studies demonstrating that interventions implemented between two- and three-months post-stroke result in significantly improved motor function. The importance of early rehabilitation and individualized care plans in maximizing recovery outcomes and improving quality of life is emphasized. The article also explores the broader context of self-management in elderly stroke survivors, addressing challenges posed by limited social support, health literacy, and disparities in access to care. Gender differences in stroke recovery among older adults are discussed, with women facing unique challenges such as higher rates of post-stroke depression and social isolation. Quality of life indicators are highlighted as essential in evaluating the effectiveness of stroke management strategies in the elderly population. The article provides recommendations for managing hypertension, dyslipidemia, diabetes, and other comorbidities in older stroke patients, as well as guidance on antithrombotic therapy, adverse drug events, and the management of dementia, osteoporosis, arthritis, and depression. The critical role of primary care providers in managing the care of stroke patients and the importance of collaboration with acute care providers and specialists are emphasized. Socioeconomic challenges faced by older stroke survivors, particularly women, are addressed, and the importance of developing an effective, actionable care plan in collaboration with the patient and their caregiver is highlighted.